2012 IEEE International Conference on Acoustics, Speech and Signal Processing (ICASSP) 2012
DOI: 10.1109/icassp.2012.6288110
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of one-dimensional transforms in coding motion compensation prediction residuals for video applications

Abstract: In video coding, motion compensation prediction provides significant increases in overall compression efficiency. The prediction residuals are typically treated as images and compressed by applying two-dimensional transforms such as the two-dimensional discrete cosine transform (2D-DCT). Previous work has found that the use of directionadaptive one-dimensional discrete cosine transforms (1D-DCTs) in coding motion compensation residuals can provide significant additional bitrate savings. However, this requires … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 6 publications
2
4
0
Order By: Relevance
“…Table 4.2 shows the relative coefficients saving with respect to using only 2D-DCT. These results are consistent with the Bjontegaard-Delta bitrate results reported in [5]. The coefficients saving, as well as the bitrate saving, increases when more transforms are used.…”
Section: Comparison With R-d Performancesupporting
confidence: 91%
See 2 more Smart Citations
“…Table 4.2 shows the relative coefficients saving with respect to using only 2D-DCT. These results are consistent with the Bjontegaard-Delta bitrate results reported in [5]. The coefficients saving, as well as the bitrate saving, increases when more transforms are used.…”
Section: Comparison With R-d Performancesupporting
confidence: 91%
“…Qualitatively, this result is consistent with the rate-distortion performance reported in [5], where these transforms are incorporated into a H.264 video coding system. The preserved energy is related with the distortion present in a compressed video sequence, and the number of coefficients used roughly indicates the number of bits in coding a residual image.…”
Section: Comparison With R-d Performancesupporting
confidence: 88%
See 1 more Smart Citation
“…In the work reported in [14]- [16], it is observed that many one-dimensional anisotropic structures arise in motioncompensated residuals. By modeling the motion-compensated residuals with one-dimensional first-order Markov models along a certain direction, a set of one-dimensional transforms of many directions is derived for encoding motioncompensated residuals.…”
Section: Previous Researchmentioning
confidence: 99%
“…Although some recent studies [10], [11] design function based global mapping curves for the 8-bit conversion and uses typical codecs for residue coding, they do not consider the local characteristics of residue blocks for encoding. However, in well-studied motion compensated LDR video coding [12], [14], it is verified that the residue blocks exhibit local anisotropic characteristics, which are more efficiently compressed with directional transforms than the traditional 2-D DCT.…”
Section: Introductionmentioning
confidence: 99%